Effects of brown bear (Ursus arctos) odour on the patch choice and behaviour of different ungulate species - Noell, Sonja (2013)
The return of large predators to regions where they were previously extirpated has created a need for knowledge about their effect on prey species, not only their lethal but also their behavioural or risk effects. In this study the behavioural risk effects of brown bear (Ursus arctos) were tested on fallow deer (Dama dama), roe deer (Capreolus capreolus), red deer (Cervus elaphus), moose (Alces alces) and wild boar (Sus scrofa). This was done by using patches of fur to simulate the presence of the novel predator (brown bear), a novel nonpredator (reindeer (Rangifer tarandus) and no fur as control. These three treatments were then compared. The response variables measured were increased vigilance, decreased feeding time and change in patch use. The results for fallow deer supported the hypothesis that there are fewer individuals present during the bear treatment (change in patch use). Red deer and roe deer changed the individuals present during treatments as well but they were least present during the reindeer treatment and most during control. The results for roe deer support the hypothesis that there is more time spent on vigilance behaviour during the bear treatment by showing more ‘sniffing in the air’ behaviour during bear treatment than during reindeer and control treatments. As well as showing more ‘combined vigilance’ during bear treatment than during reindeer treatment (increased vigilance). The results for wild boar support the hypothesis that there is less feeding behaviour during bear treatment by spending less time on ‘feeding on the ground’ during bear treatment than during control treatment (decreased feeding time). The hypothesis that feeding height is an aspect of vigilance behaviour and is therefore influenced by the bear odour was not supported. The fact that every species reacted differently shows that studying risk effects in this manner outside under natural conditions is possible but requires detailed knowledge of species behaviour to be able to tailor experiments exactly right to detect these effects.